Gestão tecnológica: um estodo de caso no setor sucroalcooleiro. - Pedro, Edilson da Silva (2003)
The opening of Brazilian economy made the sugar and alcohol industries undertake the reorganization process of their productive structures aiming to increase their competency in product differentiation and in productive and market diversification in order to face the incitement of competition. Considering this scenario, the purpose of the dissertation is to analyze technological qualification in the company and to suggest policies for the construction of a model of technological management in order to reinforce the company so that it becomes able to face the competition and the setorial markets. The contributions of this chapter are: 1) identification of the strategic resources for technological qualification; 2) survey of decision making processes for technological acquisition and learning; and 3) evaluation of practices and management means and, therefore, indication of a reference model for technological management of the company. To structure this work, a research model was elaborated taking into account the revision of literature regarding the competitiveness of Brazilian agroindustry as well as theoretical approaches of technological qualification and management of companies. The method used on the field research was an exploratory and qualitative one based on the study of only one case. It is emphasized that the research model is presented as a contribution acquired from the dissertation and that it can be used for investigations in the future. The results of this work constitute a contribution for the determination of conditions for dynamical efficiency of the agroindustry. The conclusion is that the sugar and alcohol company studied should formalize a process for definition of its technological strategy aiming the industrial market, as well as to maintain a structure for technological management. For this, it is proposed a model of qualification and technological management, considering the technological resources of the company and its position on the productive and supply chains in which it is inserted. It is believed that the case study of the problem in one company can be used as reference by other agroindustrial companies and by new researches on this theme.